Relationships between clubshaft motions and clubface orientation during the golf swing. Issue 3 (3rd July 2017) - Takagi, Tokio; Yokozawa, Toshiharu; Inaba, Yuki; Matsuda, Yuji; Shiraki, Hitoshi
Abstract: Since clubface orientation at impact affects ball direction and ball spin, the ability to control clubface orientation is one of the most important skills for golfers. This study presents a new method to describe clubface orientation as a function of the clubshaft motions (i.e., swing plane orientation, clubshaft angle in the swing plane, and clubshaft rolling angle) during a golf swing and investigates the relationships between the clubshaft motions and clubface orientation at impact. The club motion data of driver shots were collected from eight skilled golfers using a three-dimensional motion capture system. The degrees of influence of the clubshaft motions on the clubface orientation were investigated using sensitivity analysis. The sensitivity analysis revealed that the swing plane horizontal angle affected the clubface horizontal angle to an extent of 100%, that the clubshaft angle in the swing plane affected both the clubface vertical and horizontal angles to extents of 74 and 68%, respectively, and that the clubshaft rolling angle affected both the clubface vertical and horizontal angles to extents of -67 and 75%, respectively. Since the method presented here relates clubface orientation to clubshaft motions, it is useful for understanding the clubface control of a golfer.